2006
DOI: 10.1530/eje.1.02065
|View full text |Cite
|
Sign up to set email alerts
|

Influence of methyltestosterone postmenopausal therapy on plasma lipids, inflammatory factors, glucose metabolism and visceral fat: a randomized study

Abstract: Background: There has been a growing interest in treating postmenopausal women with androgens. However, hyperandrogenemia in females has been associated with increased risk of cardiovascular disease. Objective: We aimed to assess the effects of androgen replacement on cardiovascular risk factors. Design: Thirty-seven postmenopausal women aged 42-62 years that had undergone hysterectomy were prospectively enrolled in a double-blind protocol to receive, for 12 months, percutaneous estradiol (E 2 ) (1 mg/day) com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 69 publications
(49 reference statements)
0
16
0
1
Order By: Relevance
“…Experimental data suggest direct effects of testosterone on body composition, lipid levels and glucose metabolism. We postulate that increased androgenicity contributes to the accumulation of visceral fat and impairment of glucose metabolism, creating a vicious circle, whereby the increase in insulin and fat tissue in turn promote the production of 123 Surgical T Transdermal (patch) 300 mg per day 24 weeksBraunstein et al 124 Surgical T Transdermal (patch) 150/300/450 mg per day 24 weeksSimon et al 125 Surgical T Transdermal (patch) 300 mg per day 24 weeksDavis et al 126 Surgical T Transdermal (patch) 300 mg per day 24 weeksShifren et al 120 Natural T Transdermal (patch) 300 mg per day 24 weeksNathorst-Boost et al 127 Natural T Transdermal (gel) 10 mg per day 3 monthsBurger et al 128 Natural/surgical T Implant 50 mg  1 6 weeks -Davis et al 122 Natural/surgical T Implant 50 mg per 3 months 24 months k fat mass Farish et al 129 Surgical T Implant 100 mg  1 6 monthsHickok et al 130 -MT Oral 1.25 mg per day 6 months k HDL-C Watts et al 131 Surgical MT Oral 2.5 mg per day 24 months k HDL-C, triglycerides Basaria et al 132 Natural/surgical MT Oral 2.5 mg per day 16 weeks k HDL-C, triglycerides m fibrinogen Dobs et al 133 Natural/surgical MT Oral 2.5 mg per day 16 weeks k HDL-C, triglycerides, fat mass Lobo et al 134 Natural/surgical MT Oral 1.25 mg per day 16 weeks k HDL-C, triglycerides Warnock et al 135 Surgical MT Oral 1.25 mg per day 8 weeks k HDL-C, triglycerides Leao et al 136 Surgical MT Oral 1.25 mg per day 12 months k HDL-C m visceral fat mass Barrett-Connor et al 137 Surgical MT Oral 1.25 mg per day 24 months k HDL-C, triglycerides Raisz et al 138 Natural/surgical MT Oral 2.5 mg per day 9 weeks k HDL-C, triglycerides Penotti et al 139 Natural TU Oral 40 mg per day 8 months k HDL-C, m pulsatile index (PI)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental data suggest direct effects of testosterone on body composition, lipid levels and glucose metabolism. We postulate that increased androgenicity contributes to the accumulation of visceral fat and impairment of glucose metabolism, creating a vicious circle, whereby the increase in insulin and fat tissue in turn promote the production of 123 Surgical T Transdermal (patch) 300 mg per day 24 weeksBraunstein et al 124 Surgical T Transdermal (patch) 150/300/450 mg per day 24 weeksSimon et al 125 Surgical T Transdermal (patch) 300 mg per day 24 weeksDavis et al 126 Surgical T Transdermal (patch) 300 mg per day 24 weeksShifren et al 120 Natural T Transdermal (patch) 300 mg per day 24 weeksNathorst-Boost et al 127 Natural T Transdermal (gel) 10 mg per day 3 monthsBurger et al 128 Natural/surgical T Implant 50 mg  1 6 weeks -Davis et al 122 Natural/surgical T Implant 50 mg per 3 months 24 months k fat mass Farish et al 129 Surgical T Implant 100 mg  1 6 monthsHickok et al 130 -MT Oral 1.25 mg per day 6 months k HDL-C Watts et al 131 Surgical MT Oral 2.5 mg per day 24 months k HDL-C, triglycerides Basaria et al 132 Natural/surgical MT Oral 2.5 mg per day 16 weeks k HDL-C, triglycerides m fibrinogen Dobs et al 133 Natural/surgical MT Oral 2.5 mg per day 16 weeks k HDL-C, triglycerides, fat mass Lobo et al 134 Natural/surgical MT Oral 1.25 mg per day 16 weeks k HDL-C, triglycerides Warnock et al 135 Surgical MT Oral 1.25 mg per day 8 weeks k HDL-C, triglycerides Leao et al 136 Surgical MT Oral 1.25 mg per day 12 months k HDL-C m visceral fat mass Barrett-Connor et al 137 Surgical MT Oral 1.25 mg per day 24 months k HDL-C, triglycerides Raisz et al 138 Natural/surgical MT Oral 2.5 mg per day 9 weeks k HDL-C, triglycerides Penotti et al 139 Natural TU Oral 40 mg per day 8 months k HDL-C, m pulsatile index (PI)…”
Section: Discussionmentioning
confidence: 99%
“…An increase in lean body mass and decrease in fat mass have been reported after coadministration of methyltestosterone 133 and testosterone implants. 122 In contrast, Leao et al 136 described an increase in body weight and visceral fat mass after the addition of 1.25 mg methyltestosterone to transdermal estradiol therapy.…”
Section: Postmenopausal Testosterone Therapymentioning
confidence: 97%
“…In contrast, Lellano et al (60) reported that testosterone provided cardiovascular protection, whereas other authors found neither an increased cardiovascular risk nor cardiovascular protection (61-63). Therefore, the effect of testosterone on the cardiovascular system remains inconclusive.…”
Section: Discussionmentioning
confidence: 92%
“…It has also been noticed that free testosterone was not significantly corrected with triglycerides and HDL [52,55,56], the two lipids most frequently associated with the metabolic syndrome. A more recent study shows that combination of low-dose oral methyltestosterone and percutaneous oestradiol for 1 year only affects adversely HDL cholesterol and enhances visceral fat but does not result in significant increase of the components of metabolism syndrome, including glucose metabolism, other lipids, inflammatory markers or blood pressure [59].…”
Section: Metabolic Syndromementioning
confidence: 99%